Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1364/prj.7.001175
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state Mamyshev oscillator

Abstract: We present the first design and analysis of a solid-state Mamyshev oscillator. We utilize the phase-mismatched cascaded quadratic nonlinear process in periodically poled lithium niobite waveguide to generate substantial spectral broadening for Mamyshev modelocking. The extensive spectral broadening bridges the two narrowband gain media in the two arms of the same cavity, leading to a broadband mode-locking not attainable with either gain medium alone. Two pulses are coupled out of the cavity and each of the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…7a and 7b. The temporal walk-off between the signal and the pump manifests itself into the enhanced oscillatory tails on either side of the pump [42], depending on the sign of D1. Thus, the corresponding pump spectrum exhibits apparent spectral fringes.…”
Section: Effect Of Walk-offmentioning
confidence: 99%
“…7a and 7b. The temporal walk-off between the signal and the pump manifests itself into the enhanced oscillatory tails on either side of the pump [42], depending on the sign of D1. Thus, the corresponding pump spectrum exhibits apparent spectral fringes.…”
Section: Effect Of Walk-offmentioning
confidence: 99%
“…In 2019, Nie et al reported the first numerical study on a solidstate MO, using a phase-mismatched cascaded quadratic nonlinear process [101][102][103][104] to solve the problem caused by different gain media in the two arms of the MO. [105] In particular, periodically poled lithium niobate was used to further broaden the spectrum to bridge the spectral distance between the two gain media. Thus, they obtained pulses with a repetition rate of 100 MHz, energy of 25.3 nJ, 10 dB bandwidth of 2.1 THz, and a pulse duration of 322 fs.…”
Section: Solid-state Momentioning
confidence: 99%
“…[13]. In another instance, Liu et al demonstrated an all solid-state Mamyshev oscillator for the first time [15]. In 2021, Zhou et al realized Mamyshev mode-locked oscillation output based on an all-fiber seed injection structure with a peak power of 1.15 MW [16].…”
Section: Introductionmentioning
confidence: 99%